Students' Beliefs toward Mathematics as Related to Their Performance in College Algebra - Garcia, Gary C. (JPAIR Multidisciplinary Research, 2012)
The study was to determine the beliefs of SLSU-San Juan BSED freshmen towards mathematics and their performance in college algebra. Data gathered were analyzed and interpreted using Weighted Mean, Percentages, Pearson r, and the Point Biserial coefficient of correlation. Findings showed that students' educational background is 62% and 38% from public and private respectively. Majority (66%) strongly agreed that mathematics is a challenging subject and 34% considered the latter as one of the difficult subjects. Relationship between beliefs about mathematics and performance in college algebra is statistically significant at 0.05. Relationship between students' educational background and performance in college algebra was found to be not significant. The study proved that male students have better performance in college algebra than female. Students with positive beliefs about mathematics performed better in the subject. Educational background of the students was not a determinant for having good performance in college algebra. Considering the result of the study, teaching development program focusing on giving the importance of belief in teaching college algebra was recommended. Thus, values formation towards mathematics will be integrated in lesson planning to build positive beliefs.
Keywords: Students' performance in Algebra; beliefs; gender and educational background